2014
DOI: 10.4319/lo.2014.59.4.1421
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning between benthic and pelagic nitrate reduction in the Lake Lugano south basin

Abstract: We evaluated the seasonal variation of denitrification, anaerobic ammonium oxidation (anammox), and dissimilatory nitrate reduction to ammonium (DNRA) rates in the sediments and the integrative N (and O) isotopic signatures of dissolved inorganic nitrogen (DIN) compounds in the overlying water column of the monomictic Lake Lugano south basin. Denitrification was the dominant NO { 3 reduction pathway, whereas the contribution of anammox and DNRA to total benthic NO { 3 reduction was , 6% and , 12%, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 52 publications
(86 reference statements)
5
36
0
Order By: Relevance
“…The columns in the box chart represent the log number of the hzsB gene copy (copies g −1 dry soil). For all boxplots, black center lines represent the median and box edges are the first and third quartiles comparable to that reported in rivers (Zhao et al 2013), lakes (Schubert et al 2006;Wenk et al 2014), paddy soils (Zhu et al 2011;Yang et al 2015), and other estuaries (RisgaardPetersen et al 2004;Rysgaard et al 2004;Engström et al 2005), but lower than that generally detected in marine ecosystems (Tamdrup and Dalsgaard 2002;Brabandere et al 2014). Based on our results, N loss attributed to anammox was estimated to reach an average value of 9.70 × 10 5 t N per year on the basis of sediment weight, study area, and anammox average rate obtained from slurry incubations.…”
Section: Discussionmentioning
confidence: 89%
“…The columns in the box chart represent the log number of the hzsB gene copy (copies g −1 dry soil). For all boxplots, black center lines represent the median and box edges are the first and third quartiles comparable to that reported in rivers (Zhao et al 2013), lakes (Schubert et al 2006;Wenk et al 2014), paddy soils (Zhu et al 2011;Yang et al 2015), and other estuaries (RisgaardPetersen et al 2004;Rysgaard et al 2004;Engström et al 2005), but lower than that generally detected in marine ecosystems (Tamdrup and Dalsgaard 2002;Brabandere et al 2014). Based on our results, N loss attributed to anammox was estimated to reach an average value of 9.70 × 10 5 t N per year on the basis of sediment weight, study area, and anammox average rate obtained from slurry incubations.…”
Section: Discussionmentioning
confidence: 89%
“…Here we have restricted our discussion to the top 50 m of the water column. See Wenk et al (2014) and Wenk et al (2016) for details about N cycle dynamics in the redox transition zone.…”
Section: Resultsmentioning
confidence: 99%
“…Denitrification rates determined in a parallel study were relatively high under the truly anoxic conditions observed in October 2010 (28.2 ± 23.7 µmol N h −1 m −2 ; Wenk et al, 2013b), once redox gradients and, presumably, the microbial community had stabilized. At that time and also under anoxic conditions in August 2010, up to 15 % of total NO − 3 that was reduced was released as N 2 O without being completely reduced to N 2 .…”
Section: Water Column Characteristicsmentioning
confidence: 85%